Need for monitoring and maintaining sustainable marine ecosystem services - Carstensen, Jacob (Frontiers in Marine Science, 2014)
Increases in human population and their resource use have drastically intensified pressures on marine ecosystem services. The oceans have partly managed to buffer these multiple pressures, but every single area of the oceans is now affected to some degree by human activities. Chemical properties, biogeochemical cycles and food-webs have been altered with consequences for all marine living organisms. Knowledge on these pressures and associated responses mainly originate from analyses of a few long-term monitoring time series as well as spatially scattered data from various sources. Although the interpretation of these data can be improved by models, there is still a fundamental lack of information and knowledge if scientists are to predict more accurately the effects of human activities. Scientists provide expert advices to society about marine system governance, but such advices should rest on a solid base of observations. Nevertheless, many monitoring programs around the world are currently facing financial reduction. Marine ecosystem services are already overexploited in some areas and sustainable use of these services can only be devised on a solid scientific basis, which requires more observations than presently available.